2011
DOI: 10.1097/brs.0b013e3181f40ddd
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Low Back Pain in Active Duty United States Military Service Members

Abstract: Study Design. Epidemiological study. Objective. To investigate the incidence and risk factors for developing low back pain in active duty military population to include age, sex, race, and rank, and military service. Summary of Background Data. Low back pain is among the most common musculoskeletal conditions worldwide and is estimated to affect nearly two-thirds of the US population at some point in their lives. Low back pain is a multifactorial disease and many risk factors have been implicated including age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 46 publications
9
81
1
2
Order By: Relevance
“…The lower back was the body part with the highest prevalence of pain among police officers. In agreement with our findings, previous studies have also observed a high prevalence of pain in the lower back region followed by the neck and dorsal region among military soldiers (18) and police personnel (15) . The lower back is a common site of MSD symptoms, a condition that can lead to a high level of disability (19) .…”
Section: Methodssupporting
confidence: 93%
“…The lower back was the body part with the highest prevalence of pain among police officers. In agreement with our findings, previous studies have also observed a high prevalence of pain in the lower back region followed by the neck and dorsal region among military soldiers (18) and police personnel (15) . The lower back is a common site of MSD symptoms, a condition that can lead to a high level of disability (19) .…”
Section: Methodssupporting
confidence: 93%
“…3,9,34,35 Similar to previous studies, we found that back pain is associated with age (born before 1960 vs . 1970–1979), being female, being enlisted, being overweight or obese, being former or current smokers, and engaging in heavy versus light work.…”
Section: Discussionsupporting
confidence: 89%
“…Younger bodies are more resistant to musculoskeletal injuries and are not as likely as older bodies to suffer injuries resulting from chronic overuse that comes with the aging process. Along these lines, other research has shown that among active duty personnel suffering from lower back pain, older service members had higher rates of back pain compared to younger service members [35]. We have no way of knowing the age at which the neck/back injury occurred and cannot say whether it happened during or after military service.…”
Section: Resultsmentioning
confidence: 98%